The Effect of Corporate Governance, Firm Size, and Dividend Policy on Firm Value - Fajrianti Fajrianti; Ibram Pinondang Dalimunthe (Petra International Journal of Business Studies, 2025)
The valuation of a firm serves as a crucial metric for investors, as it encapsulates the entity's total performance and market perception.  This study assesses the impact of corporate governance, firm size, and dividend policy on corporate value.  Corporate governance is assessed using the ASEAN Corporate Governance Scorecard (ACGS); company size is quantified by the natural logarithm of total assets (SIZE); dividend policy is evaluated by dividends per share (DPS); and company value is determined by the price-to-book value (PBV) ratio.  This research employs a quantitative methodology.  The population comprises non-cyclical consumer sector firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, amounting to 125 companies.  A purposive sample was conducted, yielding 69 companies and 345 data points.  Panel data regression analysis was performed using EViews 12.  The study's findings indicated that firm size adversely affects firm value, whereas the dividend policy positively influences it.  Conversely, corporate governance does not exert a substantial impact on the company's worth.